2015
DOI: 10.1093/ije/dyv096.163
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Height in Adolescence: A Comparison of Methods for Estimating the Age at Peak Height Velocity.

Abstract: Background: Controlling for maturational status and timing is crucial in lifecourse epidemiology. One popular non-invasive measure of maturity is the age at peak height velocity (PHV). There are several ways to estimate age at PHV, but it is unclear which of these to use in practice. Aim: To find the optimal approach for estimating age at PHV. Subjects and methods: Methods included the Preece & Baines non-linear growth model, multi-level models with fractional polynomials, SuperImposition by Translation And Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…The results show that the SITAR growth curve model works well with growth in puberty, because it explicitly estimates these two parameters in individuals, along with a third parameter representing their mean size. Simpkin et al compared several alternative growth curve models for height in puberty, and they also concluded that SITAR was useful in providing unbiased estimates of age at peak height velocity (Simpkin et al 2017). But that said, the more detailed ALSPAC analysis has brought to light the existence of a midgrowth spurt at around 9 years in the later-maturing boys.…”
Section: Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the SITAR growth curve model works well with growth in puberty, because it explicitly estimates these two parameters in individuals, along with a third parameter representing their mean size. Simpkin et al compared several alternative growth curve models for height in puberty, and they also concluded that SITAR was useful in providing unbiased estimates of age at peak height velocity (Simpkin et al 2017). But that said, the more detailed ALSPAC analysis has brought to light the existence of a midgrowth spurt at around 9 years in the later-maturing boys.…”
Section: Study Findingsmentioning
confidence: 99%
“…A strength of SITAR is its ability to sort individuals by APV (Simpkin et al 2017). Thus it is easy to use the global model to split the ten thousand ALSPAC children into nine groups by sex, based on their timing random effects, and then analyse these local groups separately.…”
Section: Alspacmentioning
confidence: 99%
“…In the second stage of analysis, the individual random effects derived from the SITAR models were transformed to internal Z-scores, by sex, to allow for easier comparisons between outcomes with different units of measurement. Linear regression models were used to investigate variation in size, timing and intensity according to SEP group and date of birth in the R programming language and software environment for statistical computing (21) . Models were outcome (size, timing, intensity of each measure) and sex specific.…”
Section: Discussionmentioning
confidence: 99%
“…Size, timing, and intensity are also estimated as fixed effects, so the random effects have mean zero (Cole et al, ). SITAR has been shown to provide an unbiased estimate of APV (Simpkin, Sayers, Gilthorpe, Heron, & Tilling, ). The SITAR formula is: yit=αi+h()tβiexpnormalγi Where y it is height for subject i at age t , h ( t ) is a natural cubic spline curve of height vs age, and α i , β i , and γ i are subject‐specific random effects Cole et al ().…”
Section: Methodsmentioning
confidence: 99%